Optimization of The Potential of Petirtan Melunjung Waterfall in Belanga Village Through Digital Marketing - KURNIAWATI, Ni Putu Ayu Tika; PUTRA, I Wayan Gede Yogiswara Darma; DEWI, Anak Agung Istri Krisna Gangga (Community Services: Sustainability Development, 2024)
Belanga Village, located in Kintamani District, Bangli Regency, Bali, is known for its stunning natural beauty, especially Mount Batur and Lake Batur. This village features characteristics such as quality orange and coffee farming, the serene Petirtan Melunjung waterfall, and close access to the Kintamani centre for tourists. In Belanga Village is the Petirtan Melunjung Waterfall, a captivating place with a tranquil atmosphere and deep Balinese spiritual and cultural essence. Despite facing challenges like inadequate infrastructure and suboptimal marketing, lecturers and KKN students from Warmadewa University are working to provide training and assistance to the local tourism awareness group (Pokdarwis) on digital marketing and content creation in the form of videos and photos. This training will likely increase tourist visits, both domestic and international, to the Petirtan Melunjung waterfall and optimize the village's tourism potential. This can also serve as a natural tourist attraction to enjoy the beauty of Belanga Village, Kintamani.